(untitled) (Journal of Dhaka Medical College, 2021)
Introduction: Peritonitis secondary to gastrointestinal perforation is one of the commonest surgical emergencies encountered all over the world. This study was done to highlight the spectrum of perforation peritonitis encountered in surgery unit of Dhaka Medical College Hospital. Method: It was observational prospective of 100 cases of perforation peritonitis treated in our hospital. All cases of perforative peritonitis whether spontaneous, infective or neoplastic pathology were included in this study. Results: The maximum numbers of patients were in age group between 31 to 40 years (39 %) with mean age 35 years. Male female ratio was 9:1. The most common aetiology of perforation peritonitis was peptic ulcer disease (73%) followed by enteric fever (12%), appendicitis (10%), tuberculosis (3%) and malignancy (2%). The most common sites of perforation were in descending order of frequency - first part of the duodenum (65%), terminal ileum (12%), appendix (10%), gastric antrum (9%), jejunum (3%) and rectum (1%). Abdominal pain (100%) and vomiting (81%) were the most common symptoms while tachycardia (96%), muscle guard and rigidity (100%) were the common signs. Approximately 15-20% presented late with features of shock. Mortality rate was 2% and was significantly high in patients coming hospital late. Conclusion: Gastrointestinal perforations are one of the most common surgical emergencies. Duodenal perforations are most common. Ileal perforations secondary to enteric fever have highest morbidity. Early recognition and timely appropriate intervention is very important in reducing morbidity and mortality. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 106-109